Organização e gestão escolar: uma análise do conselho escolar na rede pública municipal de Cascavel - Carozzi, Elizangela Silva (2015)
Our aim of carrying out this job is to present an analysis of the School Council implemented in the city of Cascavel in 2012. Our research object, the School Council, is part of the Nacional Programme of School Councils Strengthening (PNFCE) which was created in 2004 during the first Luiz Inácio Lula da Silva‘s government. This programme proclaims to promote the democratic management through the school community participation, for this, the programme offers education courses for the role performed by counsellor. Understanding that it is a programme guided by public policies and it‘s not a movement which emerged from society, this study tries to reflect about the limit and possibility of the school community participation in a democratic management through an instrument that is the School Council. In order to develop this job it‘s been made a bibliographical research, a documental analysis and a field research, thus, the job is organized in three chapters. In the first chapter we try to understand the articulation among Business Administration, Public Administration and School Administration, in order to build elements for subsidizing our analysis in the way how the society participation movement has been incorporated. In the second chapter we recover some aspects which allow us to understand the School Council grounds and the PNFCE analysis as well as its implementation in public municipal schools of Cascavel. In the third chapter, we present the field research data which was accomplished through interviews and questionnaires with public municipal schools‘ principals, other School Council‘s members, and with the president of the Municipal Council of Education of Cascavel, the president of the Commission of Studying and Implementation of the School Council and member of a Nacional Articulator Group of School Councils Strengthening (GAFCE). To search elements for field research there were observations in Seminaries, education courses for counsellors and School Councils meetings. Our solicitude is to rescue the research questions and to put forward the limit and possibility of a School Council inside of a public school of the research field management, recovering essential aspects of the community participation